Analysis Rollover Condition of Tractor Semitrailer while Turning Maneuver with High Forward Speed - Ta, Tuan Hung; Duong, Ngoc Khanh (Old Journal, 2020)
Nowadays, there are many tractor semitrailer vehicle accidents caused by lateral instabilities, which may be classified into two types: yaw instability and rollover. The rollover of tractor semitrailer frequently occurs while directional maneuvers at high forward speed. In this paper, a full dynamic model of tractor semitrailer is developed based on Multi-body System Method and Newton–Euler equations. The rollover condition is based on the load transfer ratio which corresponds to the load transfer between the left and the right sides of the vehicle. This model is applied to determine the rollover condition of the tractor semitrailer while turning maneuvers on the high forward speed.